2020
DOI: 10.12995/bilig.9202
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’nin Yaratıcı Şehirleri

Abstract: Yaratıcı şehirler, yaratıcı mesleklerde çalışan yaratıcı sınıfı kendisine çeken, eğitim düzeyi yüksek insanların yoğun olduğu, yüksek teknolojili endüstrilere sahip, farklılıklara hoşgörülü şehirlerdir. Gelecek ekonomilerin gücü, yaratıcı şehirlerin gelişmesinin altında yatmaktadır. Çünkü yaratıcı şehirlerin temelinde, gelişme ve büyümenin öncüsü olan yaratıcılık vardır. Bu bağlamda, çalışmanın amacını da, Türkiye'nin şehirlerinin yaratıcılık seviyeleri ve gelişmişlik düzeyleri arasındaki ilişkinin irdelenmesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…In Esen & Atay (2020) empirical study performed on the scale of Turkish cities, they identified the creative cities of Turkey and claimed that if the creativity potential of the cities increases, their development will also improve, which will in the end, contribute to Turkey's development.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…In Esen & Atay (2020) empirical study performed on the scale of Turkish cities, they identified the creative cities of Turkey and claimed that if the creativity potential of the cities increases, their development will also improve, which will in the end, contribute to Turkey's development.…”
Section: Related Literaturementioning
confidence: 99%
“…The Location Quotient (LQ) was used in the calculation of the creative class. The Location Coefficient, which is also used in mapping the creative sectors in many studies (Esen & Atay, 2020), is obtained by dividing the number of people working in the creative sectors within the geographical area of interest by the total employment in that geographical location. Here, number of people working in creative sectors in province of j is denoted as Lij, while Lj is the total number of employees in province of j, the total number of employees in the creative industries nationwide is Li and finally the total number of employees in the entire country is L.…”
Section: Talent Componentmentioning
confidence: 99%
See 1 more Smart Citation
“…Seçilmiş (2015)'in çalışmasında Türkiye'de yaratıcı endüstrilerin kümelenme yoğunlaşma oranı LQ analizi sonuçlarına göre İstanbul, Ankara, Van ve İzmir yoğunlaşmanın en yüksek olduğu iller olarak belirtilmiştir. Esen & Atay (2020) ekonomik büyümenin 3T'si olan teknoloji, tolerans ve yetenek belirleyicilerine göre yapılan çalışmasında üç alt endeksin bir araya getirilip oluşturulan yaratıcı endeksine göre Ankara ve Kocaeli (0,963) birinci olurken, onları Eskişehir (0,938), İstanbul (0,926) ve İzmir (0,905) takip etmektedir. Yetenekte Ankara (1,00), İstanbul (0,975) ve İzmir (0,932); Teknolojide Kocaeli (0,984), Ankara (0,914) ve Eskişehir (0,893) ilk sıralarda görülürken, Tolerans endeksinde ise Tekirdağ (0,018), Gümüşhane (0,015) ve Antalya (0,012) yer almaktadır (Ekinci Hamamcı, 2020).…”
Section: Introductionunclassified